Digitalisasi Pembukuan Kas Berbasis Aplikasi Mobile Menggunakan Pendekatan Desain Thinking - Redjeki, Rara Sriartati; Murti, Hari; Supriyanto, Edy; Ardhianto, Eka; Wahyudi, Eko Nur (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
Cash recording plays an important role in the sustainability of MSME businesses. The problems faced by MSMEs are the lack of good cash recording and the lack of ability to learn difficult accounting science. This study provides a solution in the form of creating a mobile application-based cash recording. The method used is the design thinking approach. The form of evaluation used is using the Technology Acceptance Model technique. The results obtained are that the design thinking approach is able to solve MSME problems in recording cash from the user's side, and the results of the application usage survey state that the acceptance of the implemented technology shows a good value with an average of 9.4 agreeing that the application is acceptable